Voltage regulation using embedded generation at distribution system [electronic resource] - Abdul Hafiz Abdul Basir, 1986- (2009)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2009